Sayings and anecdotes with other popular moralists - Diogenes the Cynic pproximately 323 B.C (Oxford University Press, 2012)
"Diogenes the Cynic is famed for walking the streets with a lamp in daylight, looking for an honest man. His biting wit and eccentric behavior were legendary, and it was by means of his renowned aphorisms that his moral teachings were transmitted. He scorned the conventions of civilized life, and his ascetic lifestyle and caustic opinions informed the Cynic philosophy and later influenced Stoicism. This unique edition also covers his immediate successors, such as Crates, his wife Hipparchia, and the witty moral preacher Bion. The contrasting teachings of the Cyrenaic school, founded by Aristippos, a pleasure-loving friend of Socrates, complete the volume, together with a selection of apocryphal letters."--Publisher's website.